ANALISIS PROKSIMAT KEPITING PASIR (Ocypode Cursor) SEBAGAI SUMBER MAKANAN BERGIZI BAGI MASYARAKAT PESISIR DI KECAMATAN SALAHUTU PULAU AMBON - Tuaputty, Hasan; Leiwakabessy, Fredy; Arini, Ine; Kubangun, Muhammad Tarmizi; Latupeirissa, Louvenska (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background: The use of the Ocypode Cursor sand crab as a source of nutritious food for coastal communities in the Salahutu District area is because this marine animal is found living in sandy substrates along the coast and can be used as a source of nutritious food for coastal communities. Methods: Water content measurement was carried out using the oven method. Determination of ash content is carried out using the dry ashing method. Determination of fat content was carried out using the Soxhlet method. Analysis of protein levels using the Kjeldahl micro method. Results: The results of proximate analysis of sand crab for 100 grams of meat showed a water content of 79.72%, ash content of 6.82%, fat content of 7.5%, protein content of 15.7%. Conclusion: The results of the analysis show that there is a significant regression according to the regression provisions y = a + bx= 3,266 + 0.016, and the value of R2 = 0.802, even the analysis also shows that there is a significant influence according to the value of df = 24-22 = 2 with the value of F = 44,588 with a significance level of 000, < p 0.05, this means that there is a significant influence between the availability of the Ocypode cursor sand crab population in its habitat and Ocypode cursor as a source of nutritious food for the community (OcMGz).